Authentication protocols of remote desktop services - Teo, Hui Ling. (2013)
Remote desktop access is the ability to get accesses to a computer from a remote distance. It allows users fully control and access the remote computer as if they were sitting in front of the computer. For this reason, remote desktop application creates potential security threats over insecure network, such as communication channel could be eavesdropped and the message transmitted could be modified even impersonation attacks could be mounted. Chris Hopen, co-founder of TappIn, said “The largest underlying problem with remote access technologies isn't with remote access; its poor identity validation and weak authentication”.